REPRESENTATION OF UOC, OCU AND ROC ON FRENCH-LANGUAGE MEDIA RESOURCES IN THE CONTEXT OF THE RUSSIA’S FULL-SCALE INVASION - Krasniak , Yevheniia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is devoted to the study of lexical means of representing Ukrainian Orthodox churches as compared to that of the Russian Orthodox Church. The object of the research is French-language news published after 24.02.2022. Main Ukrainian Orthodox Churches were enumerated; it was shown the relevance of linguistic researches connected with them. The author describes the current circumstances of Ukrainian Orthodox communities during the war, focuses on the importance of the religious landscape in Ukraine as a whole and, on the other hand, shows the role of ROC in spreading untrue and manipulative information throughout Russia and the world. All these tendencies are reflected in French-language media, although not by analogous means, inasmuch as each and every news media resource uses different methods and lexical means according to two main criteria. Those are its socio-political viewpoint and secularity level. The analysis of news articles about the modern Ukrainian Orthodox landscape seems relevant under the latest conditions of a rising academic interest in religion. The article deals with leading tendencies in the French-language news covering mentioned issues as well as with lexical means used in the representation of those. Main linguistic and sociocultural challenges of Francophone journalists were mentioned. Personal contribution: observing the representation of Ukrainian Orthodoxy as opposed to Russian Orthodoxy within francophone media, which can be useful for translators as well as for researchers. _____________ References: • Ukrayinskyy svit v yoho relihiynykh vymirakh: kolektyvna monografiya, za red. prof. L. Fylypovych ta A. Aristovoyi (Kyyiv: Svit znan’. Instytut filosofii imeni H. S. Skovorody NAN Ukrainy, 2022), 196. • Boyko, N., Rousselet, K. Les Eglises ukrainiennes: Entre Rome, Moscou et Constantinople. Le Courrier des pays de l’Est 1045 (2004): 39-50. • Fylypovych, Liudmyla. The realities of current Orthodox life in Ukraine during the Russian-Ukrainian war. Studia Universitatis Babeș-Bolyai Theologia Catholica Latina 68 (2023), 7-25. • Parashchevin, Maksym. Changes in the confessional identification of the orthodox in Ukraine in the conditions of Russian aggression. Conference: Sociology – Social Work and Social Welfare: Regulation of Social Problems (2023): 82-87. • A Kyiv, la petite mort du patriarcat orthodoxe de Moscou, https://www.liberation.fr/international/europe/a-kyiv-la-petite-mort-du-patriarcat-orthodoxe-de-moscou-20230411_LUHGC24UIBC3DPBGZNPPX5BFLE/ • Analyse comparative: « l’Église orthodoxe ukrainienne est dans les faits plus autocéphale que l’Église orthodoxe d’Ukraine», https://orthodoxie.com/analyse-comparative-leglise-orthodoxe-ukrainienne-est-dans-les-faits-plus-autocephale-que-leglise-orthodoxe-dukraine/ • Ce qu’il faut savoir sur l’Église orthodoxe ukrainienne, https://orthodoxie.com/ce-quil-faut-savoir-sur-leglise-orthodoxe-ukrainienne/ • Comment les évangéliques américains et l’Église orthodoxe russe ont contribué à alimenter l’agenda anti-LGBTQ+ en Europe, https://fr.euronews.com/my-europe/2023/07/24/comment-les-evangeliques-americains-et-leglise-orthodoxe-russe-ont-contribue-a-alimenter-l • En Ukraine, une autre guerre fait rage entre les églises orthodoxes, https://www.lexpress.fr/monde/europe/en-ukraine-une-autre-guerre-fait-rage-entre-les-eglises-orthodoxes-YMGDORVBQBCRTKVDIPKGVUSCIQ/ • Homélie du patriarche d’Alexandrie Théodore II à l’occasion de sa concélébration avec le métropolite Épiphane, primat de l’Église orthodoxe d’Ukraine (autocéphale), https://orthodoxie.com/homelie-du-patriarche-dalexandrie-theodore-ii-a-loccasion-de-sa-concelebration-avec-le-metropolite-epiphane-primat-de-leglise-orthodoxe-dukraine-autocephale/ • Kiev: Condamnation d’un métropolite de l’Église orthodoxe d’Ukraine, https://www.cath.ch/newsf/kiev-condamnation-dun-metropolite-de-leglise-orthodoxe-dukraine/ • Kiev confisque le siège de l’Eglise orthodoxe ukrainienne, https://www.cath.ch/newsf/kiev-confisque-le-siege-de-leglise-orthodoxe-ukrainienne/ • «La guerre d’Ukraine est le catalyseur de la crise que traverse l’Église orthodoxe», https://fr.aleteia.org/2022/03/28/la-guerre-dukraine-est-le-catalyseur-de-la-crise-que-traverse-leglise-orthodoxe/ • L’Eglise orthodoxe d’Ukraine abandonne le calendrier julien, https://fr.aleteia.org/2023/06/06/leglise-orthodoxe-dukraine-abandonne-le-calendrier-julien/ • La Hongrie de Viktor Orban, soutien dévoué de l’Église orthodoxe russe, https://www.geo.fr/geopolitique/la-hongrie-de-viktor-orban-soutien-devoue-de-leglise-orthodoxe-russe-212137 • Le patriarche Kirill, un chef de l’Église orthodoxe russe très politique, https://www.france24.com/fr/europe/20230106-qui-est-le-patriarche-kirill-le-chef-de-l-%C3%A9glise-orthodoxe-russe • Ukraine : échauffourées à Kiev entre certains croyants de l’Eglise orthodoxe et la police, https://www.rtbf.be/article/ukraine-echauffourees-a-kiev-entre-certains-croyants-de-leglise-orthodoxe-et-la-police-11224143 • Ukraine: Les pressions sur l’Eglise orthodoxe ukrainienne s’accentuent, https://www.cath.ch/newsf/ukraine-les-pressions-sur-leglise-orthodoxe-ukrainienne-saccentuent/ • Vladimir Poutine à la reconquête de l’Église autocéphale ukrainienne, https://fr.aleteia.org/2022/03/03/vladimir-poutine-a-la-reconquete-de-leglise-autocephale-ukrainienne/